Analysis of Oil Palm Leaves Potential as an Alternative Raw Material for Paper Production - Ledya Upara Slivina; Nurcahyono Nurcahyono; Julsento HP Julsento (Tropical Plantation Journal, 2026)
The global paper industry faces a structural challenge due to excessive dependence on wood as its primary raw material, contributing to accelerated deforestation and tropical forest ecosystem degradation. Amid these environmental pressures, utilization of lignocellulosic biomass from plantation waste has emerged as a strategic and sustainable alternative. Indonesia, the world's largest palm oil producer, generates massive volumes of palm leaf waste that remain largely underutilized. This study aims to analyze the potential of oil palm leaves (Elaeis guineensis Jacq.) as an alternative raw material for paper production, encompassing biomass availability. An experimental laboratory approach was employed using NaOH delignification at 100°C for 60 minutes, followed by sheet formation and testing at two composition variants: 100% oil palm leaves and a 50% oil palm leaves–50% recycled pulp blend. The 100% leaf paper exhibited a coarser texture suitable for art and craft applications, while the blended composition produced more homogeneous sheets with superior mechanical strength for eco-packaging. These findings confirm that oil palm leaves represent a technically feasible, economically advantageous, and environmentally sustainable biomass feedstock as a partial wood substitute in the paper industry.